Biofunctionalization of Glass‐ and Paper‐Based Microfluidic Devices: A Review. Issue 19 (7th August 2019) - Shakeri, Amid; Jarad, Noor Abu; Leung, Ashlyn; Soleymani, Leyla; Didar, Tohid F.
Abstract: Biofunctionalization of microchannels is of great concern in the fabrication of microfluidic devices. Different substrates such as glass slides, papers, polymers, and beads require different biofunctionalization approaches granting the utilization of microfluidics in several biomedical applications. Covalent immobilization of biomolecules inside the microchannels is achieved by chemical modification of the surface such as silanization or introducing different coupling agents. Although creating biointerfaces that are covalently bonded to the microchannel surface necessitates multiple steps of surface modification and incubation times, it bestows a robust biointerface capable of withstanding high shear stresses and harsh conditions without dissipating the biofunctionality. Regarding the applications that do not require robustness and long‐term stability, noncovalent attachment of biomolecules such as van der Waals and hydrophobic interactions are adequate to successfully create a functional biointerface. This review summarizes the various biofunctionalization approaches used in the most common microfluidic substrates: glass and paper. In addition, several biofunctionalization examples are proposed and described in detail along with their associated applications. Abstract : Incorporation of glass‐ and paper‐based microfluidics in biomedical applications such as biosensors and organs‐on‐chips necessitates the need for immobilization of biomolecules on the microchannel surface. This review comprehensively explains various biofunctionalization techniques such as silanization process to create functional biointerfaces on the surface of the microchannels.